Wind tunnel test of a ducted fan micro air vehicle during hover flight - Tan, Yi Xiang. (2010)
This study was focused on a ducted fan micro air vehicle (MAV) that combines the exceptional hover capabilities of rotary wing aircraft with the endurance and speed performance of fixed wing aircraft. The purpose of this research was to evaluate the aerodynamic performance of the ducted fan MAV during hover flight, and subsequently investigate the effects of the various configurations on the control effectiveness of the ducted fan MAV. The Main Aircraft Laboratory wind tunnel was used to test the full scale model of the ducted fan MAV at various configurations at zero wind speed. One configuration was the single propeller motor configuration with its control surfaces varied, and the other configuration was the contra-rotating propeller motor configuration with its control surfaces varied. For the single propeller motor configuration, it was determined that the stators had insufficient control power to counter the induced rolling moment from the motor and propeller, and the elevons (acting as elevators) were more effective in the stators’ absence. Also, it was established that the differential elevon (acting as aileron) configuration, in the stators’ absence, failed to provide sufficient rolling moment to counter the induced rolling moment. Therefore, the single propeller motor configuration was found to be ineffective in providing roll control as a whole. In addition, it was found that within a certain position range, the elevon (acting as elevator) control power remained the same, while the elevon (acting as aileron) control power had no direct dependency on the positions of the elevons. For the contra-rotating propeller motor configuration, the rear propeller cancelled the torque of the front propeller to a large extent and thus provided for excellent roll control effectiveness. As a result, the stators were removed from the configuration. It was also determined that there was no direct correlation between the position of the control surface and the control power provided within a certain position range. For both motor configurations, it was found that there was a tendency for the slipstream velocity to decrease at a distance farther behind the duct. To conclude, the contra-rotating propeller motor configuration was established to be the better configuration as it generated higher thrust at a lower RPM and produced more effective control moments.